Karakteristik Antosianin dari Kulit Buah Nipah (Nypa frutican) sebagai Pewarna Alami dengan Metode Soxhletasi - Herfayati, Putri; Pandia, Setiaty; Nasution, Halimatuddahliana (Jurnal Teknik Kimia USU, 2020)
Anthocyanin is a natural pigment that gives red colour on Nipah husk (Nypa fructican) extract. Extraction of anthocyanin compounds used the soxhletation method with independent variables were the type of solvent (aquadest and ethanol with citric acid 3% (w/v)) and extraction time (30, 45 and 60 minutes). This study aims to determine the best type of solvent and extraction time used for extraction of anthocyanin from Nipah husk. The parameters in this study include qualitative and quantitative analysis of anthocyanin (extract yield, total anthocyanin concentration, color intensity, antioxidant activity and analysis of toxicity) from Nipah husk extract. The results qualitatively and quantitatively indicate that Nipah husk extract had anthocyanin content with the highest extract yield was obtained using ethanol-citric acid 3% solvent at 60 minutes extraction time of 0.546 gram / gram. The highest total anthocyanin was obtained using ethanol-citric acid 3% solvent at 30 minutes extraction time of 226.36 mg / L. The highest color intensity was obtained using ethanol-citric acid 3% solvent at 30 minutes extraction time of 0.925. The strongest antioxidant activity (IC50) was obtained using 3% aquadest-citric acid solvent at 30 minutes extraction time of 3.569 ppm. The strongest toxicity activity (LC50) in ethanol-citric acid 3% solvent was 80.023 ppm.